Meningkatkan Hasil Belajar Matematika Siswa melalui Penerapan Model Pembelajaran Discovery Learning dengan Pendekatan Teaching at The Right Level - Dewi Kusuma Ananda, Baiq; Hj. Afifah; Junaidi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The purpose of this study is to improve mathematics learning outcomes among class IX-K students at SMP Negeri 7 Mataram through the application of the Discovery Learning model combined with the Teaching at the Right Level (TaRL) approach. This research employs a Classroom Action Research (CAR) design with a descriptive quantitative approach conducted over two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The results showed a significant improvement in students’ learning outcomes. The average score increased from 68.65 in the pre-cycle to 81.3 in the first cycle, and further to 88.1 in the second cycle. Student participation also rose from 25% in the pre-cycle to 70% in the first cycle and 95% in the second cycle. Discovery Learning provided opportunities for students to construct concepts independently through investigation, observation, and conclusion-making. Meanwhile, the TaRL approach enabled teachers to tailor the learning process according to students’ comprehension levels, making instruction more targeted and effective. Therefore, the combination of these two approaches proved effective in enhancing students’ conceptual understanding, active participation, and overall learning outcomes in mathematics